Liquid level measurement based on multi-S-bend plastic optical fiber. Issue 4 (15th July 2019) - Jing, Ning
Abstract : Purpose: This paper aims to propose a liquid level sensor with a multi-S-bend plastic optical fiber. Design/methodology/approach: The principle of liquid sensing used is based on the leakage of higher modes out of the fiber and repeated regeneration in the following bend sections. Therefore, a propagation loss was introduced in every bend section of the fiber with the loss depending on the refractive index of the environment. Findings: Therefore, a continue shift in the liquid level can be detected by observing changes in the propagation loss of the fiber. The sensor features compactness and a flexible resolution. Originality/value: Compared with the exited ones, the sensor has capability of continue liquid measurement and a greater measurement range.